'Pseudomonas saudimassiliensis' sp. nov. a new bacterial species isolated from air samples in the urban environment of Makkah, Saudi Arabia. (March 2017) - Azhar, E.I.; Papadioti, A.; Bibi, F.; Ashshi, A.M.; Raoult, D.; Angelakis, E.
Abstract: We report here the main characteristics of ' Pseudomonas saudimassiliensis ' strain 12M76_air T (CSUR P1220), a new species of the Pseudomonas genus that was isolated from air samples in the city environment of Makkah, Saudi Arabia, during the pilgrim period of Hajj 2012.